Development of conductive thermoplastic elastomer blend nanocomposites for enhanced electromagnetic interference shielding in modern electronics - Sreeja Nath Choudhury; Jasomati Nayak; Aritra Mondal; Aparajita Pal; Soumen Giri; Pallab Banerji; Narayan Ch. Das (Next Nanotechnology)
Conductive thermoplastic elastomer (TPE) nanocomposites are increasingly critical for modern electronics, combining mechanical reinforcement, electrical conductivity, and effective electromagnetic interference (EMI) shielding. This study explores a novel EPDM/HDPE blend reinforced with Vulcan XC-72 conductive carbon black (VCB) to create high-performance nanocomposites. Prepared via melt mixing, these composites exhibit uniform VCB dispersion and robust conductive networks. A percolation threshold at 20 wt% VCB enables a significant increase in DC conductivity from 10−12 S/cm to 0.03 S/cm at 40 wt% VCB. Mechanical properties also improve, with tensile strength and modulus increasing by 26.42 % and 30.44 %, respectively, at minimal filler concentrations. Thermal stability is enhanced, with VCB delaying oxidative degradation and maintaining structural integrity up to 30 wt%. In EMI shielding, the composites achieve shielding effectiveness of −26.8 dB and −29.5 dB in the X- and Ku-bands, respectively, at 40 wt% VCB. The shielding mechanism more absorption dominated as VCB forms continuous conductive pathways, ensuring superior electromagnetic wave attenuation. These results establish EPDM/HDPE/VCB nanocomposites as lightweight, flexible, and cost-effective materials for advanced EMI shielding and multifunctional applications, meeting the demands of modern communication and electronic devices.